The effect of a dynamic program on developing some cognitive-motor abilities for second grade primary school Students - M. Dunia Ali Abdulhassan (physical education and sport sciences college for women/ Baghdad University, 2021)
Research objectives are: - Preparing the kinetic games program to develop some cognitive-kinetic abilities for second grade primary students. - recognize the effect of using the Kinetic Games program in developing some cognitive abilities - the kinematic for the second elementary grade students. Research hypotheses:   -  There are statistically significant differences between pre and posttests of the experimental and control group. - There are statistically significant differences between the post-tests of the experimental and control groups and in favor of the experimental group. The experimental method was used, and the curriculum was applied to the second elementary class students (40) students, and they were randomly divided into two experimental and control groups, and at a rate of (20) students in each group, the experimental group applied the motor games program prepared by the researcher, either The control group applied the traditional physical education program of the school. The two programs were implemented with (9) educational units each and by two educational units in the week